Cu Alloy Metallization for Self-Forming Barrier Process - Koike, J.; Haneda, M.; Iijima, J.; Wada, M. (Proceedings of the IEEE International Interconnect Technology Conference, 2006)
A novel Cu-Mn alloy has been developed to self-form a diffusion barrier layer at metal/dielectric interface without depositing a conventional metal barrier layer. The integration results are reviewed first to show its excellent reliability and electrical characteristics. Selection criteria of the alloying element are delineated. The reason why Mn is better than other elements is explained in terms of thermodynamic activity. The impacts of the self-forming barrier process on the BEOL process are discussed